Otimização do processo de mineralização de compostos orgânicos utilizando sistemas eletro-Fenton e fotoeletro Fenton por irradiação UV artificial e solar - Almeida, Lucio César de (2011)
Electrochemical advanced oxidation processes based on the Fenton s reaction, such as electro-Fenton (EF) and photoelectro-Fenton (PEF) using artificial and solar UV irradiation were employed in the treatment of effluents containing organic compounds (the textile dye AR 29 acid red 29, the drug paracetamol and the herbicide MCPA 2-methyl-4- chlorophenoxyacetic acid). Furthermore, kinetic studies of degradation of these compounds were performed, using factorial design in order to analyze simultaneously the influence of the parameters current, initial concentration of the catalyst Fe2+ and pH as well as the response surface methodology in order to optimize the experimental conditions. Finally, chromatographic techniques were also used for identification and quantification of the intermediates of the degradation process, among which aromatic compounds, carboxylic acids and inorganic ions. For the three investigated compounds, it was found that the main oxidant was the hydroxyl radical, OH produced by the Fenton s reaction between the catalyst Fe2+ added and the H2O2 electrogenerated by the O2 reduction at the surface of the diffusion air cathode as well as by the photolysis of hydroxylated Fe3+ species. Additionally, the use of the UV radiation, either by artificial or solar source, promoted the fast removal of Fe3+ complexes formed with carboxylic acids which were not actually removed by the OH radical. In the case of AR 29 dye, the highest efficiency was obtained for the PEF process (TOC total organic carbon removal of 95%), followed by EF process; the anodic oxidation presented the lowest performance. For paracetamol and MCPA, investigated only by the PEF process, values of TOC removal of 75 % and 74 % for the optimal conditions at 120 min electrolysis were obtained, respectively. Moreover, MCE mineralization current efficiency values of 71% for paracetamol and 72% for MCPA with EC energy consumption values of 93 kW h kg-1 TOC (7.0 kW h m-3) and 87.7 kW h kg-1 TOC (6.6 kW h m-3) were obtained, respectively. Finally, using distinct liquid chromatography techniques in order to identify and quantify the generated intermediates, plausible mechanisms for degradation of the three investigated compounds up to their complete conversion to CO2 and water were proposed.